A pilot study using flash continuous glucose monitoring in patients with type-2 diabetes on multiple anti-diabetic agents during Ramadan. Issue 6 (November 2018) - Bashir, Mohammed; Elhadd, Tarik; Ali, Hamda; Baagar, Khaled; Abdel Hakam, Ibrahim A.; Al-Mohanadi, Dabia H.S.; Naem, Emad; Al Abdulla, Amina; Mohammed, Kawsar; Abou-Samra, Abdul-Badie
Abstract: Background: This study aims to examine the incidence of hypoglycaemia, based on activity, during Ramadan in patients with type 2 diabetes mellitus who were on were on three or more anti-diabetic medications. Methods: Type 2 diabetes patients who fasted during Ramadan and were on three or more anti-diabetic medications were studied for two weeks using flash glucose monitoring. The patients were asked to document all episodes of hypoglycaemia and were classified as active or sedentary according to their daytime activity. Results: The study included 16 patients of whom 10 were active and 6 were sedentary. There were 13 males and 3 females; mean age was 53.4 ± 6.4 years; mean diabetes duration was 15 ± 5.9 years, and mean HbA1C was 7.9 ± 1.3%. Over the two weeks; there were 7.9 episodes of hypoglycaemia recorded per patient; 50% of which were asymptomatic. There was no difference at baseline in age, BMI, HBA1C, diabetes duration, and anti-diabetic medications between the active and sedentary groups. The active group had better glucose control; median blood glucose was (7.1 (5.1–8.5) vs 10.6 (9.6–11.5) mmol p < 0.01), mean estimated HBA1C was (6.2 ± 1.2% vs 8.3 ± 1.0%; p = 0.047). The active group had more episodes of hypoglycaemia compared to the sedentary group (11.6 vs 1.8 hypo episode per patient/two weeks; p = 0.019); most of which were asymptomatic. Conclusion: Patients with type 2 diabetes mellitus who are on three or more anti-diabetic medications should be warned about the increased risk of asymptomatic hypoglycaemia during Ramadan. Anti-diabetic medication adjustments during Ramadan should take into account the degree of activity. Flash glucose monitoring system can help patients to fast safely during Ramadan and detect asymptomatic hypoglycaemia.